Batman & Mr. Freeze subzero - Conroy, Kevin; Zimbalist, Efrem, $d 1923- (Burbank, CA Warner Bros, 1998)
The ultimate Batman adventure explodes into non-stop, animated action when the Caped Crusader's chilling nemesis, Mr. Freeze, returns to Gotham City and kidnaps Batgirl. In their desperate quest to unravel the mystery, Batman and Robin discover Batgirl's disappearance is all part of Mr. Freeze's frigidly fiendish plot to help his dying wife. He will do whatever it takes to save her--even it if means putting Batgirl "on ice" forever
Based on an original story by Randy Rogel and Boyd Kirkland
Closed captioned for the hearing impaired
2
Keywords: Animated films; Batman (Fictitious character) -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs